In Vitro Activity of Ampicillin Plus Ceftriaxone Against Non-faecalis and Non-faecium Enterococcal Isolates With/Without VanC Phenotype: Clinical Implications for Infective Endocarditis - Javier García-González; María A. Cañas; Guillermo Cuervo; Marta Hernández-Meneses; Miguel A. Verdejo; Marta Bodro; Javier Díez de los Ríos; Oriol Gasch; Alba Ribera; Carles Falces; Andrés Perissinotti; Bárbara Vidal; et al. (Microorganisms)
(1) Background: Alternative antibiotics are needed to treat infective endocarditis (IE) caused by non-faecalis/non-faecium enterococci; we aimed to assess the in vitro activity of ampicillin plus ceftriaxone (AMP + CTR) against these enterococci and to describe its clinical efficacy in IE cases. (2) Methods: Time–kill curves with standard (ISI) and high (IHI) inocula were performed to test VanC isolates [3 E. casseliflavus (ECAS) and 1 E. gallinarum (EGALL)] and non-VanC isolates [1 E. durans (EDUR), 1 E. hirae (EHIR) and 1 E. raffinosus (ERAF)]. The narrative literature review of IE cases treated with AMP + CTR was analyzed alongside three study cases. Clinical outcomes were relapse and death. (3) Results: Ampicillin plus gentamicin (AMP + GEN) showed synergistic and bactericidal activity against most isolates. AMP + CTR was synergistic at ISI for EGALL, EDUR, and EHIR and bactericidal against EHIR. At IHI, indifferent activity was observed for all isolates. In IE cases treated with AMP + CTR, it was only effective for EDUR and EHIR. Clinical information for EGALL IE is lacking. For IE caused by ECAS and ERAF, AMP + CTR seems suboptimal or ineffective, respectively. (4) AMP + CTR cannot be recommended for treating IE due to ECAS/ERAF. In contrast, this combination was effective in IE caused by EDUR/EHIR and could be recommended.